2001
DOI: 10.1007/s002610000199
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma recurrence after percutaneous ablation therapy: helical CT patterns

Abstract: Four patterns of recurrence after percutaneous ablation procedures can be categorized on double-phase helical CT and are best depicted on arterial phase images. Knowledge of these patterns is relevant for early detection and may be helpful in understanding the recurrence mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 30 publications
3
22
0
1
Order By: Relevance
“…Seventy-seven patients (85.6%) revealed a serum AFP level of ≥20 ng/ml and/or a DCP level of ≥40 mAu/ml. The median diameter of the HCC nodule was 20 mm (range, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Liver function was classifi ed according to the Child-Pugh classifi cation.…”
Section: Clinical Features Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy-seven patients (85.6%) revealed a serum AFP level of ≥20 ng/ml and/or a DCP level of ≥40 mAu/ml. The median diameter of the HCC nodule was 20 mm (range, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Liver function was classifi ed according to the Child-Pugh classifi cation.…”
Section: Clinical Features Of Patientsmentioning
confidence: 99%
“…22 The recurrent patterns of IDR were classifi ed into two groups, single and multiple nodules (two nodules or more), because IDR of two or more nodules is observed less frequently than that of a single nodule after resection for HCC. 23 (Fig.…”
Section: Idr Of Hcc and Recurrent Patternsmentioning
confidence: 99%
“…Furthermore, post-treatment follow-up of patients was performed with liver ultrasonography in the latter study whereas triplephase CT and dynamic contrast-enhanced MRI were used routinely in the present study. Catalano et al 21 found that at least 50 per cent of HCCs recurred after percutaneous ablation therapy, despite initial imaging and biopsy-proven evidence of successful ablation 21 -23 . Others have reported even higher recurrence rates of 81 per cent 24 and 96 per cent 25 .…”
Section: Discussionmentioning
confidence: 98%
“…The follow-up of patients undergoing these treatments is generally based on imaging studies such as magnetic resonance imaging (MRI) [10,11] or computed tomography (CT) [12], with only few doubtful cases being studied by biopsy to assess whether complete necrosis of the neoplastic tissue has been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Il follow-up dei pazienti sottoposti a questi trattamenti è generalmente affidato a metodiche di diagnostica per immagini come la RM [10,11] o la TC [12]; solo in alcuni casi dubbi si ricorre alla biopsia per verificare l'effettiva necrosi completa del tessuto neoplastico.…”
Section: Introduzioneunclassified